2021
DOI: 10.1021/acs.jproteome.1c00437
|View full text |Cite
|
Sign up to set email alerts
|

Proximity Labeling, Quantitative Proteomics, and Biochemical Studies Revealed the Molecular Mechanism for the Inhibitory Effect of Indisulam on the Proliferation of Gastric Cancer Cells

Abstract: Indisulam exhibits antitumor activity against several cancer cells. Although the DCAF15-indisulam-RBM39 axis has been well documented in the inhibition of cancer cell growth, it is unknown whether RBM39 degradation alone is the mechanism of action of indisulam. Here, we verified the inhibitory effect of indisulam on the proliferation of gastric cancer cells and its dependence on DCAF15. Proximity-dependent biotin labeling with TurboID and quantitative proteomics revealed that indisulam indeed promoted the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…Consistent with previous discoveries ( 32 ), RNA-binding motif protein 39 (RBM39) is the most significantly downregulated protein. It has been reported previously that RBM39 mediates the indisulam-induced cytotoxicity in several types of cancer cells ( 27 ) and the indisulam-inhibited proliferation of gastric cancer cells ( 32 ). Therefore, we focused on other potential targets.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with previous discoveries ( 32 ), RNA-binding motif protein 39 (RBM39) is the most significantly downregulated protein. It has been reported previously that RBM39 mediates the indisulam-induced cytotoxicity in several types of cancer cells ( 27 ) and the indisulam-inhibited proliferation of gastric cancer cells ( 32 ). Therefore, we focused on other potential targets.…”
Section: Resultssupporting
confidence: 89%
“…To explore the potential biological processes that indisulam might regulate in gastric cancer cells, we used label-free quantitative (LFQ) proteomics to identify proteins that are differentially regulated by indisulam following the procedure described in Figure 1 A . Briefly, AGS cells expressing DCAF15 from a previous work ( 32 ) were treated with dimethyl sulfoxide (DMSO) (control) or indisulam and lysed. Proteins in cell lysates were reduced, blocked, digested, desalted, and analyzed by Orbitrap Fusion Lumos Tribrid mass spectrometer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples for AP-MS were prepared following pulldown procedure as previously described with minor modifications 54 . Briefly, U2OS cells were lysed in RIPA buffer and the cell lysate was equally divided into two groups: (1) DMSO group (control group): the cell lysate was incubated with 20 μM biotin-labeled compound 1 ; (2) Cpmd 1 group (sample group): the cell lysate was incubated with 20 μM biotin-labeled compound 1 and 200 μM free compound 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Present the specific clusters (44992, 44993) of differential expression had potential implications for evaluating the sensitivity of radiotherapy and chemotherapy and guiding individualized drug use. Jiaqi Lu [27] revealed the molecular mechanisms by which indoquinone inhibits the proliferation of GC cells AGS, HGC27, MGC803, and SGC7901 through neighborhood labeling techniques, quantitative proteomics, and biochemical studies. Their group found that indisulam enhanced the ubiquitination and degradation of RBM39 by promoting its interaction with DCAF15, thereby inhibiting the proliferation of gastric cancer cells.…”
Section: Proteomic Screening Of Single Cell Differentially Expressed ...mentioning
confidence: 99%